Wheat bran and oat hulls have dose-dependent effects on ad-libitum feed intake in pigs related to digesta hydration and colonic fermentation. Issue 12 (14th November 2019) - Ratanpaul, Vishal; Zhang, Dagong; Williams, Barbara A.; Diffey, Simon; Black, John L.; Gidley, Michael J.
Abstract : Undigested nutrients and fermentable fibre in the distal ileum and colon stimulate intestinal brakes, which reduce gastric-emptying and digesta-passage-rate, and subsequently limit feed/food-intake. Abstract : Undigested nutrients and fermentable fibre in the distal ileum and colon stimulate intestinal brakes, which reduce gastric-emptying and digesta-passage-rate, and subsequently limit feed/food-intake. Fibre can also stimulate passage rate potentially increasing feed intake (FI). In order to experimentally determine the relationships between these two hypothesised actions of fibre, five levels of wheat-bran (WB) or oat-hulls (OH) were added to a highly digestible starch-based diet fed to pigs ad-libitum for three weeks. Average-daily-feed-intake (ADFI), faecal short-chain-fatty-acids (SCFA) and related parameters were determined at 7, 14 and 21d. A linear mixed model was fitted to FI and fermentation parameters. Overall, WB diets showed 8–11% lower ADFI (7–14d: p < 0.05; 7–21 & 0–21d: p = 0.053) than OH diets. WB diets produced over 20% more (21d: p < 0.01) SCFA than OH or Control diets. WB at 25% produced 22% more (7d: p < 0.05) SCFA than any other diet. Diets with WB at 25 and 35%, showed higher hydration capacity than any other diet ( p < 0.001). OH at 10% had an unusually low FI and a markedly higher hydration capacity. With increasing levels of OH, intake of base diet was 7% more than control at 5% OH, but 8% less than control at 20% OH. With increasing WB content, intake of base diet decreased. From these results, we propose that three mechanisms control the effects of fibre on FI: initial increase in passage rate and feed intake at low concentrations of non-swelling fibres; a depression in FI from high fibre bulk; and reduced feed intake from stimulation of ileal and colonic brakes.